Reaction of some muskmelon genotypes against Pseudoperonospora cubensis under field and artificial epiphytotic conditions - and TARSEM LAL*, P.P. SINGH, T.S. THIND (Indian Phytopathology, 2002)
During 1988-94 the reactions of 40 melon germplasm collections to P. cubensis in the field in Ludhiana, Punjab, India, and in the lab. were investigated. Most of the genotypes were susceptible or moderately susceptible although 9 genotypes showed some resistance. Genotype SP1 gave a resistant reaction in the field and was moderately susceptible in the lab. Genotypes SP2, SP3, KP2, KP7, KP9 and EC163888 were resistant in the field and exhibited yellow specks in the lab. F1 progeny from crosses of KP7, KP9 and EC163888 with Hara Madhu, EC163888XPunjab Sunehri and SP3XPunjab Sunehri were susceptible or moderately susceptible to P. cubensis. The incubation period was 6-7 d compared with 4 d in the susceptible controls (Hara Madhu and Punjab Sunehri).